Endoscopic closure of a refractory gastrocutaneous fistula using a novel over-the-scope Padlock clip following de-epithelialisation of the fistula tract. (29th September 2015) - Abraham, Arun; Vasant, Dipesh H; McLaughlin, John; Paine, Peter A
Abstract : Persistent gastrocutaneous fistula (GCF) is a difficult to manage complication following gastrostomy tube removal, with leakage resulting in distressing sequelae including cutaneous injury, infection and dehydration. Many such patients are high-risk for invasive surgery and, to date, endoscopic closure techniques, including clipping systems, have limitations. We present the case of a 62-year-old woman with persistently leaking GCF 6 months postgastrostomy tube removal, despite maximal antisecretory therapy and postpyloric feeding, and describe failed attempted endoscopic closure with conventional clips. Treatment options were discussed and informed consent was given for an attempt at endoscopic closure using a novel radial closure device ('Padlock clip') combined with surgical de-epithelialisation, with the understanding that this device has never previously been used in this setting. At follow-up 2 weeks postprocedure, the patient was asymptomatic with complete healing of the GCF. This approach has advantages over other endoscopic closure techniques and can be considered as an alternative approach to GCF closure.